تأثير ملوحة ماء الري والرش بحامض الهيومك في بعض الصفات المورفولوجية والفسيولوجية ونمو وحاصل نبات الحنطة .Triticum Aestivum L - الفهداوى، الهام خليفة محمود; الصميدعى، عبدالله عبدالجليل; الحديثى، ياس خضير حمزة (جامعة الانبار - مركز دراسات الصحراء, 2020)
أجريت تجربة أصص في قسم علوم الحياة/ كلية التربية للبنات/ جامعة الأنبار في الموسم الخريفي لعام 2018/2019 لدراسة تأثير ملوحة مياه الري والرش بحامض الهيومك في بعض الصفات المورفولوجية والفسيولوجية ونمو وحاصل نبات الحنطة صنف إباء-99. نفذت تجربة عامليه وفق تصميم القطاعات العشوائية الكاملة (RCBD) وبثلاثة مكررات. شملت الدراسة عاملين هما ملوحة مياه الري وبأربعة تركيز S0 وS1 وS2 وS3 ذات ملوحة (1.2 و3.2 و5.7 و8.3) ديسي سيمنز م-1 والعامل الثاني رش حامض الهيومك على النباتات وبثلاثة تركيزH0 وH1 وH2 وهي (0.0 و1.0 و1.5) غم لتر-1 على التوالي. أظهرت النتائج انخفاض معنوي في ارتفاع النبات والوزن الجاف للمجموع الخضري والحاصل البيولوجي للنبات ومحتوى الأوراق من الكلوروفيل أثناء الري بالمياه المالحة، إذ وصلت قيمتها إلى 41.09 سم و0.747 غم و0.849 غم نبات-1 و38.76 Spad على الترتيب، عند تركيز ملوحة 8.3 ديسي سيمنز م-1 مقارنة باستعمال المياه العذبة بينما أنخفض محتوى الكربوهيدرات معنويا عند المعاملة 8.3 ديسي سيمنز م-1، بلغت 18.71 ملغم غم-1. في حين حققت تراكيز رش حامض الهيومك زيادة معنوية في ارتفاع النبات والوزن الجاف للمجموع الخضري والحاصل البيولوجي ومحتوى الكلوروفيل في تراكيز (1 و1.5) غم لتر-1 مقارنة مع عدم الرش. أزداد معنويا تركيز النتروجين وأنخفض تركيز الفسفور والبوتاسيوم في الأجزاء الخضرية لنبات الحنطة عند رفع نسبة الملوحة في مياه الري، بينما أدت تراكيز الرش بحامض الهيومك إلى زيادة معنوية في تركيز النتروجين والفسفور والبوتاسيوم.
A pots experiment was conducted at the Department of Biology/College of Education for Girls/University of Anbar during autumn season of 2018-2019 to study the effect of the salinity irrigation water and spray by humic acid in some of morphological, physiological, growth and yield traits of wheat cv. IPa. The experiment was randomized complete block design (RCBD) with three replications. The first factor was assigned for irrigation by saline water at four level (S0, S1, S2 and S3), while the second factor was the foliar spraying of humic acid in three level (0.0, 1.0 and 1.5 g l-1). The results showed that there was significant reduction in plant height, vegetative dry weight, biological yield and chlorophyll leaves content when the plants were irrigated by saline water approached to 41.09 cm, 0.747 g, 0.849 g plant-1 and 38.67 SPAD, respectively at salinity level of 8.3 ds m-1 compared with the plants which irrigated by fresh water. The total carbohydrates were significantly decreased at the treatment of 8.3 ds m-1 reached 18.71 mg g-1. Spray levels humic acid achieved a significant increase in plant height, dry weight of the vegetative part, biological yield and chlorophyll leaves content sprayed at 1.0 and 1.5 g l-1 compared to no sprayed. Nitrogen concentration was significantly increased, while both phosphorus and potassium were decreased in the vegetative parts of wheat as the salinity of irrigation water increased. However, the increase of humic acid levels led to significant increasing in nitrogen, phosphorus and potassium concentration.
Keywords: المحاصيل الزراعية -- العلوم الزراعية -- رى الأرض الزراعية -- نبات الحنطة